Utility of multimodal imaging in the clinical diagnosis of inherited retinal degenerations - Brian J. H. Lee; Christopher Z. Y. Sun; Charles J. T. Ong; Kanika Jain; Tien-En Tan; Choi Mun Chan; Ranjana S. Mathur; Rachael W. C. Tang; Yasmin Bylstra; Sylvia P. R. Kam; Weng Khong Lim; Beau J. Fenner (Taiwan Journal of Ophthalmology)
Inherited retinal degeneration (IRD) is a heterogeneous group of genetic disorders of variable onset and severity, with vision loss being a common endpoint in most cases. More than 50 distinct IRD phenotypes and over 280 causative genes have been described. Establishing a clinical phenotype for patients with IRD is particularly challenging due to clinical variability even among patients with similar genotypes. Clinical phenotyping provides a foundation for understanding disease progression and informing subsequent genetic investigations. Establishing a clear clinical phenotype for IRD cases is required to corroborate the data obtained from exome and genome sequencing, which often yields numerous variants in genes associated with IRD. In the current work, we review the use of contemporary retinal imaging modalities, including ultra-widefield and autofluorescence imaging, optical coherence tomography, and multispectral imaging, in the diagnosis of IRD.